2023
DOI: 10.24123/jeb.v4i1.5390
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Usefulness, Trust, and Risk on Loyalty in the TikTok Shop: Test of Consumer Satisfaction as a Mediation Variable

Abstract: Purpose: This study aims to analyze the effect of perceived usefulness, trust and risk on loyalty with consumer satisfaction as a mediating variable at the TikTok Shop.   Method: This study's research method was a questionnaire survey. The population in this study were consumers born in 1997 – 2012 (generation Z) and had used the TikTok Shop ≥ 2 times. The sample in this study was 232 respondents. The sampling technique uses a non-probability sampling technique with a purposive sampling approach wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In addition, the present study indicated a significant relationship between TAM's PU and SAT. This is somewhat similar to an earlier study conducted by Harianto & Ellyawati [109]. Harianto & Ellyawati's [109] research endeavors to assess the impact of PU, risk, and trust on customer loyalty, with consumer SAT acting as a mediating construct.…”
Section: Comparison With Other Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, the present study indicated a significant relationship between TAM's PU and SAT. This is somewhat similar to an earlier study conducted by Harianto & Ellyawati [109]. Harianto & Ellyawati's [109] research endeavors to assess the impact of PU, risk, and trust on customer loyalty, with consumer SAT acting as a mediating construct.…”
Section: Comparison With Other Studiessupporting
confidence: 52%
“…Harianto & Ellyawati's [109] study employed a survey method and collected data from 232 consumers born between 1997 and 2012 who had engaged with the TikTok Shop at least twice. Harianto & Ellyawati's [109] research findings revealed that PU lacks a positive influence on SAT and loyalty, whereas trust and risk significantly impact consumer SAT.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The results of this test are certainly unexpected research because some previous studies have shown that Perceived Usefulness has a positive and significant effect on Customer loyalty. Although unexpected, research by [18] shows the same result, namely that there is no positive effect of perceived usefulness on customer loyalty. The reason this hypothesis is rejected is because there are various other factors such as differences in sample characteristics, objects, and places of research.…”
Section: The Effect Of Perceived Usefulness On Customer Loyalty Gen Z...mentioning
confidence: 87%
“…Some researchers place trust as a moderating variable of the influence of trust on purchasing decisions (Setiobudi, Anggraeni, Teofilus, & Sandi, 2023;Qalati, Vela, Li, Dakhan, Thuy, & Merani, 2021). Other research places trust and perceived risk as independent variables on other variables as if the two are not related to each other (Jin & Lim, 2021;Meyliana, Fernando, & Surjandy, 2019;Harianto, Ellyawati, 2023;Amarullah, Handriana, and Maharudin, 2022). Meanwhile, the results of research that position trust as an independent variable of perceived risk are very few.…”
Section: Public Interest Statementmentioning
confidence: 99%